CONSTRUCTION OF BUILDINGS AND STRUCTURES ON NATURAL STRUCTURALLY DISTURBED GRUNT - Bakhromov Makhmud Mamatkhanovich (Journals Park Publishing, 2024)
The article looked at the issues of the occurrence of natural structurally disturbed grunts, their prevalence in our Republic, the need to dispose of waste of various production, the origin of unacceptable deformations in the construction of long-standing structures, non-uniformity, uneven compressibility, the formation of grunts properties, construction on Boril in them, pre-compaction for reducing and leveling compressibility in use as a floor, the application of pile foundations.
Keywords: Spill tgunts, their origin, industrial waste, deformation, sinking, birjinsliemas, compressible, compaction, leveling, pile foundations.